Law on Management and Use of State Property - The National Assembly (2008)
This Law provides for the management and use of state property at state agencies, people's armed force units, public non-business units, political organizations, socio-political organizations, socio-professional-political organizations, social organizations and socio-professional organizations (below collectively referred to as agencies, organizations and units), including working offices and other land- attached property; land use rights with regard to land for construction of working offices or non-business establishments of agencies, organizations or units; machinery, means of transport, working facilities and other kinds of property as defined by law. The management and use of state property other than those specified in Clause 1 of this Article comply with the relevant provisions of law.